(3GdehGYX GdMSfI GdMSjfjI aj eSJYed TQH GdJJf hTLQJg GdNHjKI hBdJg GdbHjMIs - (3YeGO GdOjf jMji Hf CMeO Hf eMeO Hf GdMSf GdUfYGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi MnqQe cd HOYI eNJQYI hedgjI Yf ehGYX eSJeYg GdPi Ndb GdEfSGf hYdeg GdHjGf, hejR dg GdMdGd hGdMQGe, heG jMUd Hg GdKhGH hGdBKGe s
(3BNQgG (B:s
(3ef MGd gPg GdTLQI GdNHjKI dhdG hQhO Gdfgi HGdJMQje dgG, hGddg CYde, hdG Mhd hdG bhI EdG HGddg GdYdj GdYXje, hUdi Gddg Ydi SjOfG eMeO hBdg hSde s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs